Consumer purchasing behavior for local meat among Malaysian: a conceptual paper - Ali, Norfariza Mohd; Abd Ghani, Rosmah; Shaari, Nur Fatihah; Isahak, Siti Nordiyana; Ali@Saip, Azman; Abu Bakar, Bazri (UiTM Cawangan Johor, 2025)
Malaysia has experienced significant economic growth in recent decades, and its prosperity has accounted for an increase in meat consumption. The demand for meat in Malaysia exceeds the supply, leading to a reliance on imported meat to satisfy consumers' needs. Therefore, it is important to understand the underlying consumers' preference to purchase local meat. Through a comprehensive literature synthesis and theoretical analysis, this paper endeavours to illustrate the new factors of consumers' purchasing preferences, such as best-before date, marbling, and traditional methods used in the production of local meat among Malaysians when purchasing local meat. This paper aims to provide a conceptual roadmap for understanding how Malaysian consumers evaluate information on best-before dates, marbling, and traditional methods used in production when purchasing local meat by suggesting a conceptual framework that incorporates these variables. This conceptual study seeks to lay the groundwork for future empirical research and strategic planning for local meat suppliers, enabling a more thorough understanding of the complex processes that influence consumer behavior when purchasing local meat. Keywords: Purchasing preference, local meat, consumers' preference